Geology and Wine 11. Terroir of the Western Snake River Plain, Idaho, USA - Gillerman, Virginia; Wilkins, David; Shellie, Krista; Bitner, Ron (Geoscience Canada, 2006)
SUMMARY This article explores the unique combination of factors that shape the terroir of Idaho's principal wine grape-growing district. Most Idaho wine grape vineyards are located in the Western Snake River Plain (WSRP) rift basin (~43°N, ~117°W) on soils derived from lake, river, volcanic and wind-blown sediments. The underlying Tertiary and Quaternary rocks record the geologic history of ancient Lake Idaho, its interaction with basaltic volcanism, and subsequent Pleistocene fluvial processes and catastrophic floods. The arid to semi-arid, mid-latitude steppe climate of the WSRP provides fewer growing degree days than American Viticultural Areas (AVAs) in Walla Walla, Washington and Napa Valley, California, but still allows cultivation of Vitis vinifera grapes. Other differences include lower precipitation, higher solar radiation during the growing season, and greater threat of cold injury. Wine grapes grown in the WSRP require irrigation, and irrigation is used to manage canopy size and manipulate vine physiology. Wine grape acreage in Idaho has increased dramatically since 1993 and is estimated, in 2003, at about 500 ha with the white wine cultivars Riesling, Chardonnay, and Gewürztraminer comprising about 60% of production, and Cabernet Sauvignon, Merlot and Syrah as principal red wine cultivars.